Epidemiology of extended-spectrum β-lactamases in Enterobacterales in Taiwan for over two decades - Chao, Chien-Ming; Lai, Chih-Cheng; Yu, Wen-Liang (Frontiers in Microbiology, 2023)
The emergence of antimicrobial resistance among micro-organisms is a serious public health concern, and extended-spectrum β-lactamases (ESBL)-producing Enterobacterales is one of the major concerns among antibiotic-resistant bacteria. Although the prevalence of ESBL in Enterobacterales has been increasing with time, the prevalence of ESBL could differ according to the species, hospital allocation, sources of infections, nosocomial or community acquisitions, and geographic regions. Therefore, we conducted a comprehensive review of the epidemiology of ESBL-producing Enterobacterales in Taiwan. Overall, the rates of ESBL producers are higher in northern regions than in other parts of Taiwan. In addition, the genotypes of ESBL vary according to different Enterobacterales. SHV-type ESBLs (SHV-5 and SHV-12) were the major types of Enterobacter cloacae complex, but Serratia marcescens, Proteus mirabilis, Escherichia coli, and Klebsiella pneumoniae were more likely to possess CTX-M-type ESBLs (CTX-M-3 and CTX-M-14). Moreover, a clonal sequence type of O25b-ST131 has been emerging among urinary or bloodstream E. coli isolates in the community in Taiwan, and this clone was potentially associated with virulence, ESBL production, ciprofloxacin resistance, and mortality. Finally, the evolution of the genetic traits of the ESBL-producing Enterobacterales isolates helps us confirm the interhospital and intrahospital clonal dissemination in several regions of Taiwan. In conclusion, continuous surveillance in the investigation of ESBL production among Enterobacterales is needed to establish its long-term epidemiology.